2021
DOI: 10.51304/baer.2021.5.1.33
|View full text |Cite
|
Sign up to set email alerts
|

New Record of Macrobrachium lar (Fabricius, 1798) (Crustacea: Decapoda: Palaemonidae) from Al-Hammar Marsh, Southern Iraq

Abstract: A species of freshwater prawn Macrobrachium was newly recorded from Al-Hammar marsh, Southern Iraq. Morphological features accompanied by 18 S r DNA analyses indicated that the species is Macrobrachum lar. DNA sequences of specimens of this species from the marsh is deposited at the GenBank for DNA as a new global isolate and was published by The National Center for Biotechnology Information (NCBI), the European Nucleotide Archive (ENA) and DNA Data Bank of Japan (DDBJ). M. lar inhabit deep sections of stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…This investigated description the first record of M. equidens, in Al-Hammar marsh, Southern Iraq. Several of new species of freshwater Macrobrachium were recorded in Iraq water, and M. equidens the third invasive species of Macrobrachium to be recorded in the Iraq water, after the Macrobrachium nipponense (Salman et al, 2006) and recently Macrobrachium lar (Ghazi and Hassan, 2021). In this study, presents a differential characterize of the morphological and confirmed with DNA barcoding, mitochondrial analysis COI gene was the most important key to confirm the species under this study.…”
Section: Descriptionsupporting
confidence: 68%
See 1 more Smart Citation
“…This investigated description the first record of M. equidens, in Al-Hammar marsh, Southern Iraq. Several of new species of freshwater Macrobrachium were recorded in Iraq water, and M. equidens the third invasive species of Macrobrachium to be recorded in the Iraq water, after the Macrobrachium nipponense (Salman et al, 2006) and recently Macrobrachium lar (Ghazi and Hassan, 2021). In this study, presents a differential characterize of the morphological and confirmed with DNA barcoding, mitochondrial analysis COI gene was the most important key to confirm the species under this study.…”
Section: Descriptionsupporting
confidence: 68%
“…Genus Macrobrachium Bate, 1868 (Palaemonidae) have more than twohundred and forty two species and subspecies live in different aquatic environments (De Grave and Fransen, 2011) Macrobrachium is originated in many countries excluding in Europe (Holthuis and Ng, 2010). Based on previous studies, taxonomic records of Macrobrachium from Iraq back to 2006, the first record was by Salman et al (2006) who reported Macrobrachium nipponense, and second species which Macrobrachium lar (Ghazi and Hassan, 2021). According to Choy (1984) Macrobrachium equidens has been founded in large area such as India, Southeast Asia and Islands.…”
Section: Introductionmentioning
confidence: 99%